Spies and barbarians: The Love that Didn’t Dare Say its Name in the Soviet Union - Jesus, Diego Santos Vieira de (Pontifícia Universidade Católica de São Paulo, 2010)
The goal of this article is to propose the reexamination of the accounts of the supposed benevolence of the Soviet government toward masculine homosexuality from 1917 to 1934. The decriminalization of sodomy in the early years of the Revolution did not mean that masculine homosexuality was not vulnerable to persecution. The myth of “Russian innocence” helped to construct an image of heterosexuality as the natural pattern of the social fabric.